Trunk lean and toe out gait strategies impact on lower limb joints. (2nd December 2021) - Legrand, T.; Younesian, H.; Equey, N.; Campeau-Lecours, A.; Turcot, K.
Abstract: Gait retraining as a non-invasive prospective approach to restore mechanical loading at the knee joint and slowing down knee osteoarthritis (OA) progression shows great promise. However, the impact of gait modifications such as an increase in foot progression angle (FPA) or lateral trunk lean (LTL) on the ankle and hip is not yet well understood. Thus, the goal of this study is to provide insight on the impact of FPA and LTL on the sagittal and frontal external moments at the ankle and hip of healthy participants. We hypothesize that there is an optimum, for which an increase in FPA and/or LTL minimize the knee adduction moment (KAM) without increasing significantly the frontal and sagittal external moments at the ankle and hip during gait. To test this hypothesis, 23 participants performed walking trials with modified FPA and/or LTL angles following a real-time visual feedback. The hypothesis was not confirmed and while not all the gait modifications performed by the participants in this study reduced the KAM, they significantly increased the sagittal moment at the ankle and the frontal moment at the hip. This study highlights the importance to consider the biomechanical consequences of gait modifications on the ankle and hip before considering a clinical application of gait retraining approaches.